2009
DOI: 10.1002/rra.1269
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative impacts of river engineering, Mississippi and Lower Missouri rivers

Abstract: The goal of this study was to construct a large, data-rich model to test hydrological responses to engineering modifications on over 3200 km of the Mississippi and Lower Missouri Rivers. We compiled model explanatory variables from a geospatial database quantifying construction of all bridges, wing dikes, bendway weirs, levees, artificial meander cutoffs, channel constriction and navigational dams over the past 100-150 years. Response variables were derived from 68 rated and un-rated hydrologic stations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Between 1945 and the present, the total length of wing dikes on the MMR increased from 120,400 m (cumulative length ;Maher 1964) to at least 344,000 m (Pinter et al 2010). Between 1990and 1998,500 m of new bendway weirs were built (Pinter et al 2010), and a wave of new ''chevron dikes'' are now being built and planned along the MMR (see Sect. 1).…”
Section: Implications Of a Less Engineered Rivermentioning
confidence: 95%
See 4 more Smart Citations
“…Between 1945 and the present, the total length of wing dikes on the MMR increased from 120,400 m (cumulative length ;Maher 1964) to at least 344,000 m (Pinter et al 2010). Between 1990and 1998,500 m of new bendway weirs were built (Pinter et al 2010), and a wave of new ''chevron dikes'' are now being built and planned along the MMR (see Sect. 1).…”
Section: Implications Of a Less Engineered Rivermentioning
confidence: 95%
“…Based on hydraulic principles, Yen (1995) found that for a given flood, levees raise the stage in the channel adjacent to a levee and upstream of it. On the MMR, Pinter et al (2008Pinter et al ( , 2010 and Remo et al (2009) found that levee construction was the second most important contributor to historical flood-level increases, after channel training structures. Dyhouse (1985) assessed the impact of agricultural levees on MMR flood stages, suggesting a 1.5-m levee-driven increase for the 100-year flood.…”
Section: Infrastructurementioning
confidence: 97%
See 3 more Smart Citations